2023
DOI: 10.4103/1735-3327.372652
|View full text |Cite
|
Sign up to set email alerts
|

Influence of polishing systems on surface roughness of four resin composites subjected to thermocycling aging

Abstract: Background: Surface smoothness considered to be a significant part of the appearance and success of the restorative materials. The aim of this study was to assess the influence of four different polishing systems on surface roughness of four resin composite materials when subjected to thermocycling. Materials and Methods: This research was designed as a comparative study. Four resin composites were used which are: Nanofill composite (Filtek Supreme XT),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…Due to its combined higher strength, increased aesthetics, reduced wear, colour stability, and enhanced polished surface, micro hybrid and nano hybrid composites are utilized widely nowadays. 9 This study's findings revealed several descriptive data. For the Nano hybrid composite in Group A, the mean surface roughness and standard deviation were calculated as 0.076+0.025.…”
Section: Discussionmentioning
confidence: 72%
“…Due to its combined higher strength, increased aesthetics, reduced wear, colour stability, and enhanced polished surface, micro hybrid and nano hybrid composites are utilized widely nowadays. 9 This study's findings revealed several descriptive data. For the Nano hybrid composite in Group A, the mean surface roughness and standard deviation were calculated as 0.076+0.025.…”
Section: Discussionmentioning
confidence: 72%